Should We Fear the Robot Revolution? : (The Correct Answer is Yes) - Berg, Andrew (IMF Working Papers; Working Paper ;, 2018)
We may be on the cusp of a 'second industrial revolution' based on advances in artificial intelligence and robotics. We analyze the implications for inequality and output, using a model with two assumptions: 'robot' capital is distinct from traditional capital in its degree of substitutability with human labor; and only capitalists and skilled workers save. We analyze a range of variants that reflect widely different views of how automation may transform the labor market. Our main results are surprisingly robust: automation is good for growth and bad for equality; in the benchmark model real wages fall in the short run and eventually rise, but 'eventually' can easily take generations.